Perfect 3-Colorings of The Petersen‎ Graph - Alaeiyan, Mehdi; Karami, Hamed; Siasat, Sajjad (IndoMS, 2018)
‎In this paper we enumerate the parameter matrices of all perfect 3-colorings of the Petersen graph‎.